Unfruitful Expenditure on 100 Bed Hospital at Sirauli Gausspur, Barabanki, Uttar Pradesh - CAG of India (CAG of India)
Due to lackadaisical approach of the Government, 100 bed hospital at Sirauli Gausspur, Barabanki did not come up (November 2014) even after seven years of sanction, rendering ₹ 13.77 crore spent on its construction unfruitful.